The Relationship Between Family Support and Self-Esteem of Students Class of the Faculty of Ushuluddin Adab and Da'wah IAIN Lhokseumawe In 2025 - Muhammad Munir An-Nabawi (Journal of Innovative and Creativity, 2025)
Self-esteem is an important aspect of student development that can be influenced by family support. Family support serves as a source of emotional strength that helps students face academic and social challenges. This study aims to determine the level of family support with self-esteem of students in 2025. The method used is quantitative correlation with simple random sampling technique, involving 123 student respondents. The results of the study show 1) The level of family support is in the high category of 76.4%, the medium category is 22.8%, and the low category is 0.8%. 2) The level of student self-esteem is in the high category of 44.7%, the medium category is 54.5%, and the low category is 0.8%. 3) the calculated t value > t table = 8.670 > 1.980 and the significant value is 0.00 < 0.05, so Ho is rejected and Ha is accepted, which shows that there is a relationship between family support and self-esteem of students in the class in 2025. The coefficient of determination test at the value (R²) is 0.383, which means that family support has an influence of 38.3% on student self-esteem, and the remaining 61.7% is influenced by other factors such as acceptance or appreciation, leadership or popularity and assertiveness. Thus, the higher the family support, the higher the student's self-esteem.